PENGARUH TIME BUDGET PRESSURE, KOMPETENSI AUDITOR DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT (Studi Kasus Pada KAP Kota Malang) - Uhela Mawadati; Nur Diana; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study examines the effect of time budget pressure, competence, and auditors' independence on audit quality. The population in this study are auditors who work at the Public Accounting Firm in Malang City. A total of 60 respondents were successfully collected using the purposive sampling technique. The data used are primary in the form of questionnaires distributed to the auditors of each Public Accounting Firm in Malang. Data analysis was used using Multiple Linear Regression Analysis with the Statistical Package for the Social Science (SPSS). The test results show that time budget pressure, auditor competence, and auditor independence influence audit quality. Meanwhile, partially time budget pressure does not affect audit quality. However, the variables of auditor competence and auditor independence have a significant positive effect on audit quality.Keywords: audit quality, time budget pressure, competence, and independence of auditors.